2008
DOI: 10.1159/000112884
|View full text |Cite
|
Sign up to set email alerts
|

National Suicide Rates 1961–2003: Further Analysis of Nordic Data for Suicide, Autopsies and Ill-Defined Death Rates

Abstract: Background: Concerns about the risk-benefit ratio of treatment with antidepressants in the light of recent evidence pointing to a risk of suicide induction during the course of treatment with antidepressants. These concerns have led to a series of recent studies exploring national rates of suicide and correlating these with data on antidepressant consumption. Methods: We have compared suicide rates in the Nordic countries with autopsy and ill-defined death rates, and antidepressant sales, during the period 196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
(17 reference statements)
0
17
0
1
Order By: Relevance
“…There is a general trend toward underreporting suicide worldwide, and it is difficult to accurately evaluate differences in the reported suicide rates between countries. It has been shown that suicide is affected by both social integration and imitation (25, 26), but because suicide rates and autopsy rates are also linked (27), the picture remains muddled. Based on the rankings of 34 European countries, the suicide rates among Danish men and women are ranked as numbers 20 and 10, respectively, with women having a substantially lower suicide rate than men (23).…”
Section: Discussionmentioning
confidence: 99%
“…There is a general trend toward underreporting suicide worldwide, and it is difficult to accurately evaluate differences in the reported suicide rates between countries. It has been shown that suicide is affected by both social integration and imitation (25, 26), but because suicide rates and autopsy rates are also linked (27), the picture remains muddled. Based on the rankings of 34 European countries, the suicide rates among Danish men and women are ranked as numbers 20 and 10, respectively, with women having a substantially lower suicide rate than men (23).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the quality of the national suicide rates depends on the autopsy rates [28], which may vary over time and between countries. However, this problem may affect all kind of study designs, not only ours.…”
Section: Discussionmentioning
confidence: 99%
“…Antidepressant use, per se, may be a refl ection of better maintenance treatment with recent promotion of psycho-education and primary mental health measures. Reseland et al mention that it would always be diffi cult to correlate antidepressant use with suicide rates as the actual number of people treated would bear an uncertain relationship with amount of drug consumed [ 32 ] . It is noteworthy that the eff ect of antidepressants may be limited to specifi c demographics, e. g., in the older age groups, however this requires further detailed analysis which was not within the realms of our study [ 9 , 33 , 34 ] .…”
mentioning
confidence: 99%